Human Assets Index retrospective series: 2016 update - Michaël Goujon; Sosso Feindouno (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
Human capital, a broad concept including education and health, is considered as an essential driver of development patterns and human well-being. Undernourishment, poor health and low education attainment remain considerable obstacles to economic and social progress in Developing Countries (DCs) and particularly in the Least Developed Countries (LDCs). The Millenium Development Goals adopted by the United Nations in September 2000, where five of the eight Goals relate to education or health, portray the outstanding importance of human development. This importance has been renewed with the adoption of the Sustainable Development Goals in September 2015 that maintain the goals of "zero hunger", "good health and well-being" and "quality education"..../.....
Keywords: 330